Public perception of online news: big data analysis using netlytic - Pratama, Nugra; Santoso, Edi; Ardiansyah, Ardiansyah (Institute Of computer Science (IOCS), 2024)
This research investigates people's perceptions of online news using Netlytic, a powerful big data analytics tool. By analyzing data from social media, news sites, and forums, this research aims to understand the sentiments, preferences, and behaviors of news consumers. The research uses sentiment analysis, trend identification, and data visualization techniques to present a comprehensive picture of public opinion towards online news. This methodology provides a powerful framework to uncover trends and insights that traditional research methods may miss, offering a deeper understanding of the digital news landscape.